Comparison of 3D and 2D shear-wave elastography for differentiating benign and malignant breast masses: focus on the diagnostic performance. Issue 10 (October 2017) - Choi, H.Y.; Sohn, Y.-M.; Seo, M.
Abstract : Aim: To evaluate the diagnostic performance of three-dimensional (3D) image shear-wave elastography (SWE) for differentiating benign from malignant breast masses compared to two-dimensional (2D) SWE and B-mode ultrasound (US). Materials and methods: This study consisted of 205 breast lesions from 199 patients who underwent B-mode US and SWE before biopsy from January 2014 to March 2016. Quantitative elasticity values (maximum and mean elasticity, Emax and Emean) obtained from 2D and 3D SWE (axial, sagittal, and coronal images) were reviewed retrospectively, in addition to the histopathological findings including immunohistochemistry profiles (luminal A, luminal B, human epidermal growth factor receptor 2 (HER2)-enriched, and triple-negative breast cancer) in cases of malignancy. Histopathological findings were regarded as the reference standard. The diagnostic performance of each data set was evaluated using the area under the receiver operating characteristic (ROC) curve (AUC) analysis to compare sensitivity and specificity. Results: Among 205 lesions, 105 (51.22%) were malignant and 100 (48.78%) were benign. Compared to benign masses, malignant masses had higher values of Emax and Emean on both 2D and 3D SWE, the differences of which were statistically significant ( p <0.001). The AUCs of 2D, 3D axial, and sagittal SWE were significantly higher than that of 3D coronal SWE ( p <0.05). In addition, the sensitivities of axial, sagittal, and coronal 3D SWE were all higher than that of 2D SWE for Emean (81.9%, 87.6%, and 89.5% versus 70.5%, respectively, p <0.05). Conversely, the specificity of 2D and 3D axial SWE was higher than that of 3D sagittal and coronal SWE (Emax, 84%, 83% versus 76%, 73%; Emean, 85%, 81% versus 68%, 50%, respectively, p <0.05). We also assessed changes in Breast Imaging-Reporting and Data System (BI-RADS) category 3 and category 4a lesions by adding each of the parameters for 2D and 3D SWE in B-mode US. The specificity, PPV, and accuracy of combined 2D or combined 3D SWE with B-mode US was statistically higher than that of B-mode US alone for differentiating benign and malignant lesions ( p <0.05). Conclusions: Among SWE images, 2D SWE, and 3D SWE axial and sagittal images exhibited superior diagnostic performance compared to 3D coronal images. Addition of 3D SWE images to B-mode US improved the diagnostic performance for distinguishing benign from malignant masses. Highlights: 2D, 3D axial, 3D sagittal SWE showed better performances than 3D coronal SWE. Adding 2D or 3D SWE may be useful to reduce unnecessary false-positive biopsies.